The perception of lifelong learning by adult learners under the context of education transformation in Hong Kong: a study of adult learners’ values and experiences in the Continuing Education Fund (CEF) Programme - Pua, Mei Wah Maggie (2022)
The Continuing Education Fund (CEF) was established by the Hong Kong Government in 2002 to assist the people of Hong Kong in acquiring new knowledge and skills, to enhance their competitiveness in the global labour market and ultimately to become adaptable lifelong learners. This study aims to determine in what ways the CEF affects adult learners studying the Principles of Marketing (POM) course at a tertiary institute in Hong Kong. It focuses on the programme’s impact on student motivation and course outcomes. The research also seeks to understand whether the programme increases the likelihood that participants will take part in lifelong learning when the funding ends.